Association between changes in depressive symptoms and risk of anemia: from the China Health and Retirement longitudinal study - Yucong Bi; Liping Zheng; Leping Zhang; Longyang Han; Yang Liu; Xiaowei Zheng; Chongke Zhong (BMC, 2024)
Abstract Background Previous studies have reported that anemia was associated with depression, but the association between changes in depressive symptoms and the risk of anemia was unclear. This study aimed to explore whether changes in depressive symptoms were associated with anemia among the middle-aged and elderly adults. Methods A total of 6112 patients aged 45 years and older from the China Health and Retirement Longitudinal Study (CHARLS) were included in this analysis. Elevated Depression Symptoms (EDS) was defined as the Center for Epidemiological Studies Depression Scale-10 score ≥ 10. Depression status was defined as no depressive symptom [no EDS at Wave 1 (2011-2012) and Wave 2 (2013-2014)], decreasing depressive symptoms (EDS at Wave 1, no EDS at Wave 2), increasing depressive symptoms (no EDS at Wave 1, EDS at Wave 2), persistent depressive symptoms (EDS at Wave 1 and Wave 2). Multivariable logistic regression analyses were conducted to estimate the relationships between depressive symptoms and the changes and risk of anemia. Results During the follow-up of Wave 1 and Wave 3 (2015-2016), 906 participants (14.82%) developed anemia, the multivariable-adjusted odds ratio for the depressive symptom compared with the no depressive symptom was 1.24 (95% CI, 1.12-1.58) for anemia. From Wave 2 to Wave 3, there were 828 participants (14.62%) diagnosed with anemia. Compared to participants with no depressive symptom, those with persistent depressive symptoms during Wave 1 and Wave 2 had the significantly elevated risk of anemia (odds ratio 1.44, 95% CI 1.21-1.84). Conclusions The present study demonstrated that baseline depressive symptoms and changes in depressive symptoms were associated with increased risks of anemia.